Mountain gorilla tourism generating wealth and peace in post‐conflict Rwanda. (14th June 2013) - Maekawa, Miko; Lanjouw, Annette; Rutagarama, Eugène; Sharp, Douglas
Abstract Today only around 880 mountain gorillas (Gorilla beringei beringei) inhabit the Afromontane forests shared by Rwanda, Uganda and the Democratic Republic of the Congo (DRC). In this region, mountain gorillas serve as flagship species, attracting public support and international tourists as well as drawing attention to their habitat. This paper examines the prominent issues in mountain gorilla conservation and nature‐based tourism in Rwanda in a post‐conflict recovery context. Also analyzed are the critical issues of restoring and developing the capacities of institutions, improving the transboundary dialogue, and developing cooperation for the management of natural resources.